Assessment of socio-economic profile and residents’ satisfaction living in apartments and single unit houses in Islamabad, Pakistan - Hassan, Syeda Zainab; Naeem, Malik Asghar; Waheed, Abdul; Thaheem, Muhammad Jamaluddin (International Journal of Strategic Property Management, 2019)
Cities in Pakistan, because of rapid pace of urbanization, are unable to provide adequate housing supply to cater to the needs of the people. Islamabad, the capital of Pakistan, has a population of two million with a growth rate of six percent. Construction of apartment buildings, as one of the alternatives to fulfil the housing needs, is on the rise. However, apartments are being designed without considering the needs of the residents. This research focuses on assessment of socio-economic profile and satisfaction of residents of single unit houses vis-à-vis of those living in apartments. Fried and Gleicher’s approach was used in this research. This study analysed the socioeconomic characteristics, level of satisfaction of residents; drivers and barriers that influence the residential satisfaction of residents in two types of residential units in Islamabad. This study finds that residents of both housing types were equally satisfied with housing attributes and surrounding neighborhood while the residents of single unit houses were more satisfied with facilities, maintenance and culture. This study suggests that more focus should be given to factors like open space, basic amenities, privacy while designing an apartment building.